156 A new tool to aid the differential diagnosis of physiological remodelling from cardiac pathology when assessing left ventricle and left atrial structure in male arab and black paedaitric athletes. (4th June 2021) - McClean, Gavin
Abstract : Background: Physiological remodelling of the paediatric athletes' heart can overlap with phenotypic expression of cardiomyopathies, which increase the risk of sudden cardiac death. This overlap may be compounded by BSA, race, chronological and biological age. We established nomograms and Z-scores for clinical evaluation of left ventricular (LV) and atrial (LA) structure in Arab and black paediatric athletes, accounting for the impact of BSA, race, chronological and biological age. Methods: 417 (297 Arab, 120 black) male paediatric (11-18 years) athletes, were evaluated by 2D echocardiography as per the as per British Society of Echocardiography guidelines, and biological age (by radiological X-ray) assessment. Z scores involved allometric (a*[BSA]^((b+c*chronological age) )) modelling for measures of LV structure. Results: Residual linear regression, revealed normalised measures of LV to be independent of BSA, race, chronological and biological age. Z-scores for an athlete with a specific BSA and/or chronological age can be calculated 1) visually in the nomograms provided ( figure 1 ) 2) automatically online/on the EchoCalc app ( Figure 2 ), or 3) manually from by using the specified a, b, and c mean predicted parameters and d, e, and f RSD for that parameter of LV structure from table 1 : z=(obs-(a*[BSA]^((b+c*chronological age) )) )/(d+(e*BSA)+(f*chronological age)) Conclusion: For the first time, we present BSA, race, chronological, and biological age independent nomograms and Z scores for LV, LA and Aortic size to BSA in male Arab and black paediatric athletes. Nomograms are provided to assist in the tracking of the paediatric athlete necessitating annual follow-up and online/app calculation to facilitate use in day-to-day practice ( figures 1 and 2 ). In clinical context, we propose a new tool for differential diagnosis of physiological remodelling to an indicator of cardiac pathology in the cardiac screening of the paediatric athlete. Conflict of Interest: None